2018
DOI: 10.12659/msm.907228
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Abnormal Hepatic Lipid Metabolism Induced by Chronic Intermittent Hypoxia in Rats and the Therapeutic Effect of N-Acetylcysteine

Abstract: BackgroundThe pathogenesis of chronic intermittent hypoxia (CIH)-induced abnormal hepatic lipid metabolism in rats remains unclear. Here, we investigated the therapeutic effect of N-acetylcysteine (NAC) on abnormal hepatic lipid metabolism.Material/MethodsRats were subjected to hypoxia and NAC treatment, and evaluated in terms of hepatic lipid metabolism, hepatocyte ultrastructure, oxidative stress in hepatocytes, expression of nuclear factor-kappa B (NF-κB) and inflammatory cytokines (IL-1β, IL-6, and TNFα), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The present results suggested that 4 weeks of CIH exposure induced liver fibrosis in the CIH and ciH-Vector groups, while the ciH-Vector group presented an inflammatory state with increased expression of IL-1β, il-8, McP-1, TnF-α, icaM-1 and VcaM-1. nF-κB is considered to be an oxidant-sensitive transcription factor, and activation of nF-κB promotes inflammation and multiple tissue injury in response to ciH and in liver disease conditions (31,32). Furthermore, the present results indicated that 4 weeks of ciH exposure increased nF-κB and Tlr4 expression levels in the liver.…”
Section: Discussionsupporting
confidence: 57%
“…The present results suggested that 4 weeks of CIH exposure induced liver fibrosis in the CIH and ciH-Vector groups, while the ciH-Vector group presented an inflammatory state with increased expression of IL-1β, il-8, McP-1, TnF-α, icaM-1 and VcaM-1. nF-κB is considered to be an oxidant-sensitive transcription factor, and activation of nF-κB promotes inflammation and multiple tissue injury in response to ciH and in liver disease conditions (31,32). Furthermore, the present results indicated that 4 weeks of ciH exposure increased nF-κB and Tlr4 expression levels in the liver.…”
Section: Discussionsupporting
confidence: 57%
“…These findings suggest that this type of IH can enhance the oxygen-carrying capacity and tolerance to ischemia and hypoxia of tissues, thus improving exercise endurance. Left ventricular function was assessed in isolated Abnormal liver lipid metabolism [10], liver injury [11],endothelial cell dysfunction [12], hypercholesterolemia, and lipid peroxidation [13] Positive (low-intensity IH): protects against myocardial ischemiareperfusion injury [14], prevents arrhythmia [15] Positive (low-intensity IH): prevents arrhythmia and myocardial infarction [16], improves myocardial contractile function [17], etc.…”
Section: Non-osa-ihmentioning
confidence: 99%
“…Multiple pathologic conditions can induce tissue hypoxia, which is an important mediator of lipid metabolism [ 30 , 31 ]. Chronic and acute alcohol intake stimulates hepatic oxygen consumption, and subsequently causes hepatic hypoxia, leading to Hif pathway activation.…”
Section: Discussionmentioning
confidence: 99%